Knowledge, attitude, and practice assessment toward COVID-19 among communities in East Nusa Tenggara, Indonesia: A cross-sectional study - Lee, Felix; Suryohusodo, Aileen Alessandra (Frontiers in Public Health, 2022)
Objective: This research aimed to assess the knowledge, attitude and practice towards COVID-19 among East Nusa Tenggara (NTT) population and identify associated sociodemographic factors. Methods: A cross-sectional study was performed among communities in NTT between October–November2021 using a structured questionnaire. Results: The percentages of survey respondents showing good knowledge, attitude and practice towards COVID-19 were 79.8%, 72.7%, and 94.6%, respectively. There was a significant positive, though weak, linear correlation between knowledge and practice scores (ρ=0.097; p=0.049). Knowledge was strongly associated with regency of residence (Cramer's V=0.266; p=0.010), education (Cramer’s V=0.312; p<0.001), and occupation (Cramer's V= 0.313; p<0.001). Attitude and practice had strong relationship with regency of residence (Cramer's V=0.289; p= 0.024) and education (Cramer's V=0.272; p<0.001), respectively. Conclusion: Nearly all survey participants showed good precautionary behaviours, but there was still a quarter of respondents indicated poor knowledge and attitude. There was also a positive relationship between knowledge and practice scores thereby indicating the importance of local public health advocates to distribute information uniformly especially to the groups with inadequate knowledge towards COVID-19 as a means to control the virus transmission.